The study of groups - Klein, Josephine, 1926-2018 (Routledge, 1998)
In attempting to understand the psychological aspects of the developmental process and socialisation, the distinct disciplines of sociology and psychology were brought together for the first time. Titles in the Sociology of Behaviour and Psychology set of the International Library of Sociology analyse how behaviour is formed and learned.
"First published in 1956 by Routledge and Kegan Paul, Ltd."
Keywords: Social groups.; Sociology.; Sociology; Sociologie.; sociology.; SOCIAL SCIENCE -- Anthropology -- General.; SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Sociology -- General.; Social groups